Implementasi Kebijakan Kelompok Informasi Masyarakat (KIM) Berbasis Pemberdayaan Masyarakat Kabupaten - Fitriyani, Fitriyani; Delly Maulana; Obed Bida (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
The goal to be achieved in this research is to find out the implementation of community information group (KIM) policies based on community empowerment in Paser Regency. The method used in this research is descriptive qualitative. In order to obtain data related to the required research focus, the researchers conducted interviews with the KIM chairman, KIM members and community leaders. In order to support the information obtained, the researcher also conducted field observations. The results of this study indicate that the communication established by KIM members is based on flexible timeframes, limited to communication via WhatsApp. Formal recruitment has not been optimally carried out because the KIM organization is voluntary in which the majority of its members are village officials themselves so that the resources recruited do not have the expertise in the required field, namely IT. the members do not yet have the ability to be competent in their field, considering that this organization is voluntary, the members who participate are also from the village community who do not yet have qualified skills. the organizational structure is explained that in KIM the organizational structure consists of a chairman and members where the structure is a differentiator in completing tasks and responsibilities. Obstacles faced which include the lack of incentives that make KIM members not run according to formal procedures, low understanding of journalism, low time management and low facilities and infrastructure owned.